2014
DOI: 10.1002/jez.b.22571
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics, plasticity, and evolution: How do we link epigenetic change to phenotype?

Abstract: Epigenetic mechanisms are proposed as an important way in which the genome responds to the environment. Epigenetic marks, including DNA methylation and Histone modifications, can be triggered by environmental effects, and lead to permanent changes in gene expression, affecting the phenotype of an organism. Epigenetic mechanisms have been proposed as key in plasticity, allowing environmental exposure to shape future gene expression. While we are beginning to understand how these mechanisms have roles in human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
215
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(225 citation statements)
references
References 164 publications
(211 reference statements)
1
215
0
9
Order By: Relevance
“…For example, Barshis et al (2013) provided useful long-term data on acclimation of coral species to climate change. In particular, species that can resist reprogramming during meiosis and embryogenesis, and transmit changes in DNA methylation to offspring, will help facilitate understanding of transgenerational epigenetic processes (Duncan et al, 2014). For example, Schield et al (2015) characterized methylation variation of clonal Daphnia ambigua in response to fish predator cues, showing consistent changes in the epigenome in successive generations.…”
Section: Box 4 Outstanding Questions About Epigenetically Encoded Thementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Barshis et al (2013) provided useful long-term data on acclimation of coral species to climate change. In particular, species that can resist reprogramming during meiosis and embryogenesis, and transmit changes in DNA methylation to offspring, will help facilitate understanding of transgenerational epigenetic processes (Duncan et al, 2014). For example, Schield et al (2015) characterized methylation variation of clonal Daphnia ambigua in response to fish predator cues, showing consistent changes in the epigenome in successive generations.…”
Section: Box 4 Outstanding Questions About Epigenetically Encoded Thementioning
confidence: 99%
“…Przybylo et al, 2000;R eale et al, 2003;Møller & Meril€ a, 2004;Charmantier et al, 2008). Recently, both empirical and theoretical studies have demonstrated that epigenetic variation can either independently contribute to phenotypic plasticity, or mediate a genetically encoded plastic response (Richards et al, 2010;Duncan et al, 2014). Moreover, several recent findings have shed light on the range of different roles that epigenetic variation may play during evolution.…”
Section: Introductionmentioning
confidence: 99%
“…These adaptations, or developmental plasticity, have been defined as the ability of a single genotype to give rise to several different phenotypes which, teleologically speaking, allows organisms to adapt to their surrounding environmental conditions more rapidly than possible with evolutionary changes (Duncan et al 2014). Some have suggested that the term "plasticity" was used to describe epigenetic phenomena before we had an understanding of epigenetics (Jablonski 2012).…”
Section: Developmental Origins Of Adult Diseasementioning
confidence: 99%
“…The transmission of epigenetic information is indirect when environmental signals induce a behavioral or physiological change in an organism that is preserved in subsequent generations through a non-meiotic mechanism. Transmission is direct when an environmental influence directly affects the germline cells or when the modification is mediated through the interaction of somatic cells with germline cells and is preserved through meiosis (Duncan et al 2014). Considering that heritable epigenetic variations could affect the processes of adaptation and divergence, Jablonka and Raz (2009) proposed that it is necessary to consider within evolutionary models the changes caused by the selection of epigenetic variants and changes in which an epigenetic modification drives the selection of a genetic variant.…”
Section: Perspectivesmentioning
confidence: 99%